Adsorption kinetic model of alginate gel beads synthesized micro particle-prussian blue to remove cesium ions from water. (April 2016) - Mihara, Yoshihiro; Sikder, Md. Tajuddin; Yamagishi, Hideaki; Sasaki, Takahiro; Kurasaki, Masaaki; Itoh, Shinji; Tanaka, Shunitz
Abstract: Prussian blue (PB) impregnated in alginate gel (AG) beads were synthesized in order to test their viability for removing cesium (Cs) ions from wastewater. The impregnation yields PB-AG(syn.) beads containing very fine crystals of PB incorporated into the AG beads. The interaction between PB-AG(syn.) beads and Cs ions was investigated by adsorption experiments and analyzed using Langmuir and adsorption-kinetic models. The adsorption of Cs ions onto PB-AG(syn.) beads reached equilibrium after 12 h. The maximum adsorption capacities of the PB-AG(syn.) beads were 0.557 mg bead −1 and the kinetic rate was found to be k 1  = 1.72 × 10 −1  min −1 at pH 6.0 for the pseudo first order, and 4.65 × 10 −1  bead −1  mg −1  min −1 at pH 6.0 for the pseudo second order. The effects of pH, organic acids and salts such as potassium and sodium ions onto the adsorption of Cs ions by PB-AG(syn.) beads were found insignificant and low. Consequently, the PB-AG(syn.) beads showed a high capacity for the removal of Cs ions from water.